Qualitative cross-cultural exploration of breast symptoms and impacts associated with hormonal treatments for menopausal symptoms to inform the development of new patient-reported measurement tools. Issue 3 (March 2015) - Abraham, Lucy; Humphrey, Louise; Arbuckle, Rob; Dennerstein, Lorraine; Simon, James A.; Mirkin, Sebastian; Bonner, Nicola; Walmsley, Steven; Tatlock, Sophi; Symonds, Tara
Highlights Cross-cultural interviews highlight that breast pain is a commonly experienced side effect of EPT. A range of impacts caused by breast pain/tenderness are experienced by PM women on EPT. We highlight that side effects and impacts of EPT should be considered in treatment decision-making.